Gladys Black letter to Nicholas S. Halmi regarding bird sightings, April 5, 1977 - Black, Gladyset al (1977)
Letter from Gladys Black to Nicholas S. Halmi, regarding bird sightings. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly Report of spring 1977. Epson - sheet feed/flatbed